A Survey on 3D Cameras : Metrological Comparison of Time-of-Flight, Structured-Light and Active Stereoscopy Technologies /: Metrological Comparison of Time-of-Flight, Structured-Light and Active Stereoscopy Technologies. ([2018]) - Giancola, Silvio; Valenti, Matteo; Sala, Remo
No abstract available